Mutual inhibitions between epidermal growth factor receptor signaling and miR‐124a control pancreatic progenitor proliferation. Issue 8 (7th December 2018) - Zhang, Zhenwu; Zhai, Wenjun; Liang, Jie; Chen, Zhenbao; Ma, Mingjun; Zhao, Yicheng; Liang, Yang; Li, Xuyan; Teng, Chun‐Bo
Abstract: Pancreatic stem/progenitor cells convert from a proliferative to a differentiated fate passing through proliferation cease to a resting state. However, the molecular mechanisms of cell cycle arrest are poorly understood. In this study, we demonstrated that the microRNA‐124a (miR‐124a) inhibited the proliferation of pancreatic progenitor cells both in vitro and ex vivo and promoted a quiescent state. The miR‐124a directly targeted SOS Ras/Rac guanine nucleotide exchange factor 1 (SOS1), IQ motif‐containing GTPase‐activating protein 1 (IQGAP1), signal transducer and activator of transcription 3 (STAT3), and cyclin D2 (CCND2), thereby inactivating epidermal growth factor receptor (EGFR) downstream signaling pathways including mitogen‐activated protein kinase/extracellular signal‐regulated kinase (MEK/ERK), phosphatidylinositol 3‐kinase‐protein kinase B (PI3K/AKT) and Janus kinase (JAK)/STAT3. miR‐124a blocked cell proliferation mainly through targeting STAT3 to inhibit PI3K/AKT and JAK/STAT3 signaling. Moreover, miR‐124a expression was negatively regulated by EGFR downstream PI3K/AKT signaling. These results indicated that miR‐124a and EGFR signaling mutually interact to form a regulating circuit that determines the proliferation of pancreatic progenitor cells. Abstract : In this study, we demonstrated that the microRNA‐124a (miR‐124a) inhibited the proliferation of pancreatic progenitor cells both in vitro and ex vivo and promoted a quiescent state. miR‐124a blocked cell proliferation mainly through targeting signal transducer and activator of transcription 3 (STAT3) to inhibit phosphatidylinositol 3‐kinase‐protein kinase B and Janus kinase/STAT3 signaling. Moreover, miR‐124a expression could also be inhibited by epidermal growth factor (EGF), indicating that miR‐124a and EGF signaling mutually interact to form a negative feedback circuit determining the fate of pancreatic progenitor cells.